Between public security needs and the protection of fundamental rights. Origins and evolution of “41 bis” (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
This note traces the evolution of the special imprisonment regime regulated by Article 41 bis, the so-called “hard detention” (namely the regime of isolation), from its introduction in 1986 to the present. The aim is to explain to the reader how at issue is not so much the usefulness of the so-called "hard prison" as a tool for combating organized crime as its specific modes of implementation, which can configure treatment detrimental to the dignity of prisoners.
Keywords: Mafia; 41 bis; Terrorism; Prison; Parliament